The impact of climate mitigation measures on near term climate forcers. (15th October 2019) - Turnock, S T; Smith, S; O'Connor, F M
Abstract: Here we quantify the regional co-benefits to future air quality on annual to daily mean timescales from implementing mitigation measures to stabilise future climate. Two consistent future emissions pathways are used within the composition-climate model HadGEM3-UKCA: one is a reference pathway of future economic growth and development (REF), whilst the Representative Concentration Pathway 4.5 (RCP4.5) assumes the same development pathway but stabilises anthropogenic radiative forcing at 4.5 W m −2 in 2100. Implementing greenhouse gas (GHG) mitigation measures in RCP4.5 reduces global mean air pollutant emissions by up to 30% in the 2050s, in addition to mitigating climate. Annual mean surface concentrations of ozone and PM2.5 decrease by 10%–20% from the combined reductions in emissions and climate change. The number of days exceeding the World Health Organization's (WHO) daily mean air quality standards are reduced by up 47 days for ozone and 15 days for PM2.5 over different world regions. The air quality co-benefits from mitigation measures are mainly achieved from reductions in anthropogenic emissions, although benefits can be offset due to changes in climate. In terms of anthropogenic climate forcing, while the reduction in global mean effective radiative forcing (ERF) in 2050, relative to the 2000s, due to enacting carbon dioxide mitigation measures (−0.43 W m −2 ) is enhanced by decreases in tropospheric ozone (−0.26 W m −2 ) and methane (−0.2 W m −2 ), it is partially offset by a positive aerosol ERF from reductions in aerosols (+0.35 W m −2 ). This study demonstrates that policies to mitigate climate change have added co-benefits for global and regional air quality on annual to daily timescales. Furthermore, the effectiveness of the GHG policies in reducing anthropogenic climate forcing is enhanced in the near-term by reductions in ozone and methane despite the increased forcing due to reductions in aerosols.